Pengaruh Harga, Kualitas Layanan Dan Lokasi Terhadap Keputusan Pengguna Self-Service Laundry (Studi Kasus Pada Mahasiswa di Kota Malang) - Maulida, Rizki Sofa; Diana, Nur; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study was to determine the effect of price, service quality and location on self-service laundry user decisions. Data was collected using purposive sampling from 95 respondents through a questionnaire with a Likert Scale. Data analysis was carried out using multiple linear regression and hypothesis testing (F and t tests) with the IBM SPSS ver 20 program. The results of this study indicate that simultaneously, the three variables have a positive and significant influence on user decisions (significance 0.000 <0.05). The results of the study explain that each variable price, service quality has a partial and simultaneous effect on user decisions. Keywords: The Effect of Price, Service Quality, Location and User Decisions